Associations between insulin action and integrity of brain microstructure differ with familial longevity and with age - Akintola, Abimbola A.; van den Berg, Annette; van Buchem, Mark A.; Jansen, Steffy W.; Slagboom, Eline P.; Westendorp, Rudi G.; van der Grond, Jeroen; van Heemst, Diana (Frontiers in Aging Neuroscience, 2015)
Impaired glucose metabolism and type 2 diabetes have been associated with cognitive decline, dementia, and with structural and functional brain features. However, it is unclear whether these associations differ in individuals that differ in familial longevity or age. Here, we investigated the association between parameters of glucose metabolism and microstructural brain integrity in offspring of long-lived families (“offspring”) and controls; and age categories thereof. From the Leiden Longevity Study, 132 participants underwent oral glucose tolerance test to assess glycemia (fasted glucose and glucose area-under-the-curve (AUC)), insulin resistance (fasted insulin, AUCinsulin, and homeostatic model assessment of insulin resistance (HOMA-IR)), and pancreatic Beta cell secretory capacity (insulinogenic index). 3Tesla MRI and Magnetization Transfer (MT) imaging MT-ratio peak-height was used to quantify differences in microstructural brain parenchymal tissue homogeneity that remain invisible on conventional MRI. Analyses were performed in offspring and age-matched controls, with and without stratification for age. In the full offspring group only, reduced peak-height in grey and white matter was inversely associated with AUCinsulin, fasted insulin, HOMA-IR and insulinogenic-index (all p<0.01). When dichotomised for age (≤65years & >65 years): in younger controls, significantly stronger inverse associations were observed between peak-height and fasted glucose, AUCglucose, fasted insulin, AUCinsulin and HOMA-IR in grey matter; and for AUCglucose, fasted insulin and HOMA-IR in white matter (all P-interaction<0.05). Although the strength of the associations tended to attenuate with age in the offspring group, the difference between age groups was not statistically significant. Thus, associations between impaired insulin action and reduced microstructural brain parenchymal tissue homogeneity were stronger in offspring compared to controls, and seemed to diminish with age.